2021
DOI: 10.21037/apm-21-839
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety between high-intensity focused ultrasound and uterine artery embolization for cesarean scar pregnancy: a systematic review and a meta-analysis

Abstract: Background: It was reported that high-intensity focused ultrasound (HIFU) of cesarean scar pregnancy (CSP) can locally inactivate pregnancy tissue. Uterine artery embolization (UAE) can achieve good results for CSP too. To investigate the clinical efficacy and safety of HIFU and UAE in the treatment of cesarean scar pregnancy (CSP), we conducted this research.Methods: Multiple databases were used to search for relevant studies and articles related to HIFU, UAE, and CSP. The selected literature were retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Another advantage is that the SonoVue contrast agent can distinguish non-treated tissue and left tissue blood supply. 16 Another guidance with MRI HIFU system include workstation and console, control therapy station with a computer. The MRI device contains a US transducer which is set on a mechanical arm.…”
Section: Us and Mri-guided Hifumentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage is that the SonoVue contrast agent can distinguish non-treated tissue and left tissue blood supply. 16 Another guidance with MRI HIFU system include workstation and console, control therapy station with a computer. The MRI device contains a US transducer which is set on a mechanical arm.…”
Section: Us and Mri-guided Hifumentioning
confidence: 99%
“…HIFU is the best choice for CSP patients with a high hCG level, large gestational sac, and long gestational time, especially for patients with re-pregnancy at the scar site after cesarean section, which can increase the uterine retention rate. 30 HIFU is safe, effective, precise, requires no X-ray exposure, and causes less pain in the treatment of CSP patients. It can retain the functional integrity of the uterus.…”
Section: Clinical Applications Of Hifumentioning
confidence: 99%
“…At present, many studies have shown that HIFU-a combined with curettage is safe and efficient in treating patients with CSP [ 14 , 15 ], and several studies have further reported successful re-pregnancies after this treatment [ 15 , 16 ]. However, there is insufficient comparative research evidence on subsequent pregnancy outcomes after previous CSP treatment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%